Dampak Media Sosial terhadap Perilaku Konsumtif Remaja di Era Digital - Nanang Hunaifi; Phitsa Mauliana; Ricky Firmansyah; Yunika Komalasari; R. Dewi Sulastriningsih; Srie Wijaya Kesuma Dewi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The development of information and communication technology has brought significant changes in various aspects of life, including the consumer behavior of teenagers. This study aims to examine the impact of social media on teenage consumer behavior using the Systematic Literature Review (SLR) method. Analysis of various studies shows that social media has a significant influence on teenage consumer behavior. Targeted advertisements, influencers, and social media content are the main factors influencing teenagers' purchasing decisions. Intensive use of social media is also correlated with an increase in unhealthy and excessive consumer behavior. This research highlights the importance of education on healthy social media usage, the role of families and schools in guiding teenagers, and stricter government policies regarding social media advertisements. Recommendations for further research and practical interventions are also provided to mitigate the negative impact of social media on teenage consumer behavior.